Sox9b is a key regulator of pancreaticobiliary ductal system development. - Marion Delous; Chunyue Yin; Donghun Shin; Nikolay Ninov; Juliana Debrito Carten; Luyuan Pan; Taylur P Ma; Steven A Farber; Cecilia B Moens; Didier Y R Stainier (PLoS Genetics)
The pancreaticobiliary ductal system connects the liver and pancreas to the intestine. It is composed of the hepatopancreatic ductal (HPD) system as well as the intrahepatic biliary ducts and the intrapancreatic ducts. Despite its physiological importance, the development of the pancreaticobiliary ductal system remains poorly understood. The SRY-related transcription factor SOX9 is expressed in the mammalian pancreaticobiliary ductal system, but the perinatal lethality of Sox9 heterozygous mice makes loss-of-function analyses challenging. We turned to the zebrafish to assess the role of SOX9 in pancreaticobiliary ductal system development. We first show that zebrafish sox9b recapitulates the expression pattern of mouse Sox9 in the pancreaticobiliary ductal system and use a nonsense allele of sox9b, sox9b(fh313), to dissect its function in the morphogenesis of this structure. Strikingly, sox9b(fh313) homozygous mutants survive to adulthood and exhibit cholestasis associated with hepatic and pancreatic duct proliferation, cyst formation, and fibrosis. Analysis of sox9b(fh313) mutant embryos and larvae reveals that the HPD cells appear to mis-differentiate towards hepatic and/or pancreatic fates, resulting in a dysmorphic structure. The intrahepatic biliary cells are specified but fail to assemble into a functional network. Similarly, intrapancreatic duct formation is severely impaired in sox9b(fh313) mutants, while the embryonic endocrine and acinar compartments appear unaffected. The defects in the intrahepatic and intrapancreatic ducts of sox9b(fh313) mutants worsen during larval and juvenile stages, prompting the adult phenotype. We further show that Sox9b interacts with Notch signaling to regulate intrahepatic biliary network formation: sox9b expression is positively regulated by Notch signaling, while Sox9b function is required to maintain Notch signaling in the intrahepatic biliary cells. Together, these data reveal key roles for SOX9 in the morphogenesis of the pancreaticobiliary ductal system, and they cast human Sox9 as a candidate gene for pancreaticobiliary duct malformation-related pathologies.